Analisis Hukum Dugaan Peniruan Merek Polo Terhadap Ralph Lauren Di Indonesia - Fahira Nayla; Syakira Mawlida Yazmi; Aisyah Putri Arrum; Nabila Kezia Nasrulloh; Naysila Kayla P. G.; Sitti Regita Hutomo (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Legal Analysis of the Alleged Imitation of the Polo Brand against Ralph Lauren in Indonesia The protection of well-known brands is becoming one of the important issues in intellectual property law as trademark disputes increase in global trade. One of the disputes that has attracted attention is the use of the POLO brand which has sparked debates regarding the protection of well-known brands, similarities in essence, and potential consumer confusion. This study aims to analyze the legal protection of well-known brands and examine the alleged similarities between the POLO and Ralph Lauren brands based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The research uses normative legal methods with legislative, conceptual, and case approaches. Data was obtained through literature studies sourced from laws and regulations, international legal instruments, books, scientific journals, and relevant court decisions. The results of the study show that Ralph Lauren meets the criteria as a well-known brand that obtains protection under national and international law. The analysis also shows that the use of the word "POLO" and symbols related to the sport of polo has the potential to cause similarities in the subject matter as well as the likelihood of confusion regarding the origin or affiliation of the product. Therefore, the protection of well-known brands is necessary to ensure legal certainty, protect consumers, and create healthy business competition.